PENINGKATAN KANDUNGAN ASAM AMINO HIDROLISAT TEMPE SEMANGIT MELALUI PENGGUNAAN ENZIM PROTEASE DARI DAUN KELOR (Jurnal Teknologi Pangan, 2023)
Longer time of fermentation treatment in overripe tempeh causes an increase in amino acid content in overripe tempe. The addition of protease enzymes from dial oleifera leaves to overripe tempeh will cause protein hydrolysis that leads to an increase in amino acid content..In this study, hydrolysate from overripe tempeh was made with different fermentation time variation for 2 days, 3 days, 4 days and 5 days and the addition of protease enzyme from Moringa leaves with various concentrations (0.1%, 0.15%, 0.2%, and 0.25%). Several test conducted to get physical and chemical characteristics include enzyme activity test, protein content, amino acid test, water content, and chroma. The results obtained showed that the hydrolysate from overripe tempeh that have been fermented for 5 days with the addition of 0.25% Moringa oleifera leaves purified enzymes has the highest amino acids and low protein content. The color test showed a significant difference in the values of a * and b * due to the treatment between hydrolyzed samples. The value of lightness of overripe tempeh hydrolysate for with 5 days fermentation time and an addition of 0.25% enzymes indicates a significant difference with the control sample. The moisture content obtained in this study have greater value than SNI standards. Moringa oleifera leaves purified protease enzymes purified through the stages of dialysis reach their optimum conditions at 50oC and pH 7.